PENINGKATAN KERAGAMAN WARISAN BUDAYA MELALUI WORLD HERITAGE DAY & BUGBUG CULINARY FESTIVAL 2026 SEBAGAI STRATEGI PEMBERDAYAAN UMKM DAN PARIWISATA BERKELANJUTAN DI DESA BUGBUG - I Ketut Suardana; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
This community service activity aims to raise public awareness of the diversity of cultural heritage through the implementation of World Heritage Day & Bugbug Culinary Festival 2026 as a strategy for empowering MSMEs and developing sustainable tourism in Bugbug Village, Karangasem Regency. This program is motivated by Bugbug Village's significant cultural and tourism potential, yet it still faces challenges in MSME business management and digital-based marketing. The implementation method involves several stages: outreach, training, technology implementation, mentoring and evaluation, and program sustainability. The activity involves MSMEs, indigenous communities, the younger generation, the village government, and tourists in various cultural activities, traditional culinary promotions, and digital marketing. The results of the activity indicate an increase in MSME understanding and capacity in aspects of product quality, packaging, tourism services, and the use of digital media as a promotional tool. Furthermore, the festival successfully increased community participation in preserving local culture while strengthening the appeal of cultural and culinary-based tourism. Thus, this activity is a strategic step in strengthening the synergy between MSMEs and the tourism sector to support the sustainable economic independence of local communities.